Vagabond but elusive: two newcomers to the Eastern Amazon (Araneae: Cithaeronidae; Prodidomidae) - Ruiz, Gustavo R.s.; Bonaldo, Alexandre B. (Zootaxa, 2013)
The spider clade Gnaphosoidea gathers dionychans with obliquely angled posterior median eyes with flat lenses (Platnick, 1990), which would be part of a compass mechanism rather than being used to form images (Dacke et al., 2001). Besides the Gnaphosidae Pocock, by far the most diverse family of the group (with over 2,000 species), the clade includes six other spider families, mostly recorded from Australia and Africa, such as Ammoxenidae Simon, Lamponidae Simon, Gallieniellidae Millot (with a single species from South America) and Trochanteriidae Karsch (also in Asia and two genera in South America) (Platnick, 1990; 2013). The remaining two families, Cithaeronidae Simon and Prodidomidae Simon, represent the least and the second richest gnaphosoid families, respectively.